A descriptive longitudinal analysis of the ownership structure of Spanish innovative companies - Juan Pablo Gonzales-Bustos (Revista Internacional de Organizaciones, 2016)
This descriptive study makes a longitudinal analysis of the ownership structure of Spanish companies in innovative economic sectors. Our purpose is to contribute to the inconclusive research that analyses the impact of ownership structure on innovation by describing who the main blockholders of innovative companies in Spain are, determining the influence of domestic versus foreign capital, and exploring whether there are any significant differences when different time periods and different innovative sectors are compared. We collected data from 86 Spanish companies in innovative sectors between 2003 and 2014 (inclusive) which supplied a total of 898 observations. The results confirm that Spanish capital plays a bigger role than foreign capital in the ownership structure of Spanish innovative sectors, and that concentrated ownership by the board of directors, especially by affiliated directors, is also important. There are significant differences in the ownership structure of Spanish innovative sectors. However, its evolution over time is quite stable, with the exception of the proportion of executive ownership.